Bordieuan Reading on O.Henry’s Mammon and the Archer - Betty Sianturi (Prologue: Journal on Language and Literature, 2023)
This study employs a Bordieuan framework to conduct a sociological analysis of O. Henry's short story, "Mammon and the Archer." By applying this theoretical lens, the emphasis is on the complex interplay of cultural, social, and economic capitals, contextualizing the socioeconomic context of the Gilded Age. Through this sociological examination, the present study unravels the motivations that drive the characters, exposes the underlying social hierarchies, and elucidates the pervasive influence of wealth on their actions. This analysis provides valuable insights into the era's power dynamics and class distinctions, portraying how the pursuit of material wealth shaped the lives of individuals during this pivotal period in American history. "Mammon and the Archer" by O. Henry, analyzed through Pierre Bourdieu's sociological framework, unravels the intricate relationships between cultural, social, and economic capitals. Consequently, this analysis contributes to a richer understanding of the narrative's multifaceted dimensions and prevailing relevance in a historical context.